A Randomized Trial of Iron-Biofortified Pearl Millet in School Children in India. Issue 7 (6th May 2015) - Finkelstein, Julia L; Mehta, Saurabh; Udipi, Shobha A; Ghugre, Padmini S; Luna, Sarah V; Wenger, Michael J; Murray-Kolb, Laura E; Przybyszewski, Eric M; Haas, Jere D
Abstract: Background: Iron deficiency is the most widespread nutritional deficiency in the world. Objective: The objective of this randomized efficacy trial was to determine the effects of iron-biofortified pearl millet (Fe-PM) on iron status compared with control pearl millet (Control-PM). Methods: A randomized trial of biofortified pearl millet ( Pennisetum glaucum ), bred to enhance iron content, was conducted in 246 children (12–16 y) for 6 mo in Maharashtra, India. Iron status [hemoglobin, serum ferritin (SF), soluble transferrin receptor (sTfR), and total body iron (TBI)], inflammation (C-reactive protein and α-1 acid glycoprotein), and anthropometric indices were evaluated at enrollment and after 4 and 6 mo. Hodges-Lehmann-Sen 95% CIs were used to examine the effect of the Fe-PM on iron status compared with commercially available Control-PM. Linear and binomial regression models were used to evaluate the effects of Fe-PM on iron status and incidence of anemia and iron deficiency, compared with Control-PM. Results: At baseline, 41% of children were iron deficient (SF <15 μg/L) and 28% were anemic (hemoglobin <12.0 g/dL). Fe-PM significantly increased SF concentrations and TBI after 4 mo compared with Control-PM. Among children who were iron deficient at baseline, those who received Fe-PM were 1.64 times more likely to become iron replete by 6 mo than were those receiving Control-PM (RR: 1.64, 95% CI: 1.07, 2.49, P = 0.02). The effects of Fe-PM on iron status were greater among children who were iron deficient at baseline than among children who were not iron deficient at baseline. Conclusions: Fe-PM significantly improved iron status in children by 4 mo compared with Control-PM. This study demonstrated that feeding Fe-PM is an efficacious approach to improve iron status in school-age children and it should be further evaluated for effectiveness in a broader population context. This trial was registered at clinicaltrials.gov as NCT02152150.